(untitled) (Eurasian Journal of Philology Science and Education, 2021)
In the article the work of Kazakh literature’s classic Zhambyl Zhabayev is considered. His poems are analyzed in terms of a cognitive approach, which is one of the new in modern literary study. Based on systematization of scientific works, devoted to this problem, in the article the essence, principles of this method are revealed. The author emphasizes the importance, productivity of the cognitive approach. The use of this method allowed, firstly, to more deeply reveal the psychology of the author, heroes, reader, their ideas about the surrounding reality; secondly, to understand the poet’s thinking mechanisms and their reflection at various levels of the poetics of works. In the article the ways of modeling of the lyrical hero’s inner world, peculiarities of his thinking, attitude towards the surrounding reality are described. The analysis of mental spaces, reflected in the poems of the poet. Based on a comparison of the works of Zh. Zhabaev and A. Kunanbaev, the features of the construction of his individually-authored picture of the world are revealed. The originality of his concept of being and personality is described. The system of images embodied in the works of Zhambyl Zhabayev is analyzed. The factors that influenced the poet’s worldview, his perception of the phenomena and events of reality, the peculiarities of the construction of mental spaces are revealed. On the example of studying the works of Zh. Zhabayev from the point of view of the cognitive approach, the effectiveness and prospects of this method in the study of artistic creativity, comprehension of the nature of verbal art, and the national identity of the writer are substantiated.